No evidence for quenching in quasars. Issue Volume 15:Issue S359(2020) (March 2019) - Wethers, Clare; Acharya, Nischal; De Propris, Roberto; Kotilainen, Jari; Schramm, Malte; Schulze, Andreas
Abstract: The role of quasar feedback in galaxy evolution remains poorly understood. Throughout this work, we explore the effects of negative feedback on star formation in quasar host galaxies, analysing two distinct populations of quasars. The first is a sample of high-redshift (z > 2) low-ionisation broad absorption line quasars (LoBALs) - a class of quasars hosting energetic mass outflows, in which we find evidence for prolific star formation (>750Mʘ yr –1 ) exceeding that of non-BAL quasars at the same redshift. The second is a population of 207 low-redshift (z < 0.3) quasars, in which we find an enhancement in the SFRs of quasar hosts compared to the underlying galaxy population, with no quasars residing in quiescent hosts over the last 2Gyr. Overall, we find no evidence for galaxy-wide quenching in either population, rather we suggest that the dominant effect of quasar activity is to enhance star formation in the galaxy.